Antiviral Functions of Human Immunodeficiency Virus Type 1 (HIV-1)-Specific IgG Antibodies: Effects of Antiretroviral Therapy and Implications for Therapeutic HIV-1 Vaccine Design - French, Martyn A.; Tjiam, M. Christian; Abudulai, Laila N.; Fernandez, Sonia (Frontiers in Immunology, 2017)
Contemporary antiretroviral therapy (ART) is effective and tolerable for long periods of time but cannot eradicate HIV-1 infection by either elimination of viral reservoirs or enhancement of HIV-1-specific immune responses. Boosting ‘protective’ HIV-1-specific immune responses by active or passive immunisation will therefore be necessary to control or eradicate HIV-1 infection and is currently the topic of intense investigation. Recently reported studies conducted in HIV patients and non-human primate (NHP) models of HIV-1 infection suggest that HIV-1-specific IgG antibody responses may contribute to control of HIV-1 infection. However, production of IgG antibodies with virus neutralising activity by vaccination remains problematic and while vaccine-induced natural killer cell-activating IgG antibodies have been shown to prevent acquisition of HIV-1 infection, they may not be sufficient to control or eradicate established HIV-1 infection. It is therefore important to consider other functional characteristics of IgG antibody responses. IgG antibodies to viruses also mediate opsonophagocytic antibody responses against virions and capsids that enhance the function of phagocytic cells playing critical roles in anti-viral immune responses, particularly conventional dendritic cells and plasmacytoid dendritic cells. Emerging evidence suggests that these antibody functions might contribute to control of HIV-1 infection. In addition, IgG antibodies contribute to the intracellular degradation of viruses via binding to the cytosolic Fc receptor tripartite motif containing-21 (TRIM21). The functional activity of an IgG antibody response is influenced by the IgG subclass content, which affects binding to antigens and to Fc receptors on phagocytic cells and to TRIM21. The IgG subclass content and avidity of IgG antibodies is determined by germinal centre (GC) reactions in follicles of lymphoid tissue. As HIV-1 infects cells in GCs and induces GC dysfunction, which may persist during ART, strategies for boosting HIV-1-specific IgG antibody responses should include early commencement of ART and possibly the use of particular antiretroviral drugs to optimise drug levels in lymphoid follicles. Finally, enhancing particular functions of HIV-1-specific IgG antibody responses by using adjuvants or cytokines to modulate the IgG subclass content of the antibody response might be investigated in NHP models of HIV-1 infection and during trials of therapeutic vaccines in HIV patients.